Quantified Intakes of Key Diet Components and the Risk of Developing Rheumatoid Arthritis– Results from a Nested Case-Control Study - Bäcklund, Rebecka Teresia; Bergström, Ulf; Compagno, Michele; Arvidsson, Linnea; Rydell, Emil ; 0000-0002-3643-7648; Sonestedt, Emily ; 0000-0002-0747-4562; Turesson, Carl (Annals of the Rheumatic Diseases, 2025)
Objectives This nested case–control study aimed to investigate the relationship between components of the Swedish food-based dietary guidelines (SDG) from 2015 and the risk of developing rheumatoid arthritis (RA). Methods Data were obtained from the prospective Malmö Diet and Cancer Study (MDCS) conducted 1991–1996. Diet was assessed at baseline using a validated diet history method. Incident RA cases until 2016 were identified through register linkage, followed by a validation process through review of medical records. For each case, 4 RA-free controls, matched for age, sex, and year of inclusion in the MDCS, were selected from the cohort. Adherence to the SDG was assessed using the SDG Score (SDGS) of 5 components. Multivariable logistic regression and restricted cubic splines (RCS) were applied to analyse the relationships among the SDGS, its components, and RA. Results A total of 305 incident RA cases (67% rheumatoid factor/anti-cyclic citrullinated peptide positive) were identified. Recommended intakes of vegetables and fruits (>400 g/day) and red and processed meat (<500 g/week) were associated with lower risks of RA, with multivariable-adjusted odds ratios of 0.64 (95% CI 0.43–0.94) and 0.60 (95% CI 0.38–0.97), respectively. RCS revealed a positive linear association for total intake of red/processed meat with RA development and a negative association for vegetables and fruits. The risk was higher by quartile of red and processed meat intake for seropositive, but not seronegative RA. Conclusions Higher intake of red/processed meat associated with a higher risk of seropositive RA, whereas vegetables and fruit may reduce the risk of RA overall.